A Framework for Digital Forensic in Joint Heterogeneous Cloud Computing Environment - Umar, Zayyanu; Emmanuel, Etuh (Journal of Future Internet, 2019)
The cloud computing is nowadays an embracing computing technology by many organizations, academic institutions and business centers. Resources availability, resources capacity, security are among the factors that subscriber consider while rating Cloud Service Providers when subscribing. Cloud Service Providers (CSPs) are limited in some resources, lacking some resources requested by their customers, this gave rise to the need for interconnecting multiple clouds to interoperate and share resources. The interconnected clouds can be in different features and schemes and the system can be prone to insecurity or intrusion. The architectural modeling system was used in developing framework. In this paper, a Digital Forensic Framework that can detect intrusion within heterogeneous joint clouds was developed with the architectural model and algorithm that can handle the joint clouds heterogeneity and complexity during inter-clouds resources management. This study originates a new framework and an algorithm that enable detecting crime and locating a scene of a crime for digital investigation (digital forensic) in a joined different configured cloud service providers (CSPs) platforms.